Coagulation Disorders in COVID-19: Role of Toll-like Receptors - Biswas I; Khan GA (Dove Medical Press, 2020)
Indranil Biswas,1 Gausal A Khan2 1Cardiovascular Biology Research Program, Oklahoma Medical Research Foundation, Oklahoma City, OK 73104, USA; 2Department of Physiology & Physiotherapy, College of Medicine, Nursing and Health Sciences, Fiji National University, Suva, Fiji IslandsCorrespondence: Gausal A KhanDepartment of Physiology & Physiotherapy, College of Medicine, Nursing and Health Sciences, Fiji National University, Suva, Fiji IslandsEmail gausalk@gmail.comAbstract: Coronavirus disease 2019 (COVID-19) has spread rapidly throughout the world. The range of the disease is broad but among hospitalized patients with COVID-19 are coagulation disorders, pneumonia, respiratory failure, and acute respiratory distress syndrome (ARDS). The excess production of early response proinflammatory cytokines results in what has been described as a cytokine storm, leading to an increased risk of thrombosis, inflammations, vascular hyperpermeability, multi-organ failure, and eventually death over time. As the pandemic is spreading and the whole picture is not yet clear, we highlight the importance of coagulation disorders in COVID-19 infected subjects and summarize it. COVID-19 infection could induce coagulation disorders leading to clot formation as well as pulmonary embolism with detrimental effects in patient recovery and survival. Coagulation and inflammation are closely related. In this review, we try to establish an association between virus infections associated with innate immune activation, inflammation and coagulation activation.Keywords: COVID-19, coagulation disorders, TLR3, tissue factor